Harnessing AI and robotics in humanitarian assistance and disaster response - Manzini, Thomas; Murphy, Robin R.; Heim, Eric; Robinson, Caleb; Zarrella, Guido; Gupta, Ritwik (Science Robotics, 2023)
AI and robotics can facilitate humanitarian assistance and disaster response, but partnerships with practitioners are crucial. The article discusses the potential of using artificial intelligence (AI) and robotics in humanitarian assistance and disaster response. The authors emphasize the importance of collaborations with practitioners in order to effectively harness AI and robotics for these purposes. In 2022, there were 387 natural hazards and disasters globally, resulting in significant loss of life and economic costs. Despite efforts, the AI community has faced challenges in applying computer vision and machine learning technologies to real disaster situations. The Fourth Workshop on AI for Humanitarian Assistance and Disaster Response (AI + HADR) aimed to accelerate the adoption of these technologies by bringing together experts in the field and AI research. The workshop highlighted issues such as the fragility of AI systems and the need for better human-machine interaction, including trust, transparency, and operator training. The consensus reached was that ongoing collaboration between HADR technologists and practitioners is crucial during technology development to ensure a deep understanding of the domain, alignment of objectives, and realistic assessments of technology capabilities and operational limitations.